Maternal mortality in Andaman and Nicobar group of islands: 10 years retrospective study - Indu Chawla; Mrinmoy Kumar Saha; Anis Akhtarkharvi (Wolters Kluwer Medknow Publications, 2014)
Context: Maternal mortality ratio (MMR) is an indicator of effectiveness of health care facilities for women of child bearing age group. Andaman and Nicobar (A&N) group of islands are unique as they are situated 1200 km from the mainland India. Healthcare delivery for the these islands is exclusively provided and controlled by only one authority, Directorate of Health Services, A&N Islands. GB Pant Hospital, Port Blair is the only referral hospital with round the clock specialists and surgical services. Aims: To estimate the MMR in A&N islands from 2001 to 2010, and study the causes of maternal mortality. Settings and Design: Retrospective. Materials and Methods: Data for the estimation of MMR were collected from office of Registrar of Births and Deaths, Hospital and Peripheral Health Centres. Case records of maternal deaths in GB Pant Hospital were reviewed to study the causes of death. Statistical analysis used: Proportions and Ratios. Results: Ten years average MMR for the entire island was 85.42. Analysis of 30 maternal deaths in GB Pant Hospital showed that 63.3% were due to direct obstetric causes (eclampsia 30%, hemorrhage 23.33%, sepsis 6.66%, and 3.33% amniotic fluid embolism). Of the indirect causes, anemia was the commonest (16.66%). Conclusions: The MMR of A&N islands is much lower than the national average of 250. Direct obstetric causes accounted for more than half of maternal deaths 63.33%.